Analisis Status Nitrogen Tanah Dalam Kaitannya Dengan Serapan N Oleh Tanaman Padi Sawah Di Desa Waimital, Kecamatan Kairatu, Kabupaten Seram Bagian Barat - P. S Patti; Eizabet Kaya; Charles Silahooy (Faculty of Agriculture, Pattimura University, 2013)
Nitrogen is a major nutrient for plant growth. Nitrogen function to increase vegetative growth, increase the number of tillers and increase the number of grains/clusters and increase the size of rice grain. The purpose of research was to analyze the availability of N in the soil and plant N content, and calculating fertilizer needs to increase rice productivity. Research was conducted using survey methods with an area sampling approach, conducted in October 2012 - January 2013. The research area was 590.6 ha. The soil total N ranged from very low (KP3 and 5 at 0.06% and 0.09% respectively), until low (KP 1, 2, 4, 6 and 7 at 0.14%, 0.15%, 0.13% 0.17% and 0.14% respectively. Meanwhile, the plant N sampled from the start of grain filling until harvest were low, ranged from 1% - 1.31%. The doses of fertilizer needed to sustain 5 ton ha-1 rice for the next planting season by adding Urea were as much as KP 1 (224.3 kg ha-1), KP 2 (224.25 kg ha-1), KP 3 (224.7 kg ha-1), KP 4 (224.35 kg ha-1), KP 5 (224.55 kg ha-1), KP 6 (224.15 kg ha-1) and KP 7 (224.3 kg ha-1).